Study on Views of Respondents About Help By Male Members In Pri Works: Examining the Support and Views of Women Leaders in Male-Dominated Societies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In male dominated traditional society, women are not considered as aleader of full capacity, capability, and potentials. Women have to observepurdah during PRI meeting also. Feeling of shy and hesitation is there. thefeeling of women leaders about the support of male counterparts. 159 (71.00%)respondents say that male members support and help the female while remaining65 (29.00%) opined that their male counterparts don’t support them anddiscourage them. Majority 58 (40.84%) of women Panches respond that they getsupport from male members followed by 40 (28.17%) who get help from malemember. While 44 (30.98%) Panches told that they don’t get support and arediscouraged by them. At the same level 11 (73.34%) women Sarpanches viewed thatthey get support and help from male members, 4 (20.00%) believe neither theyget support or help from males.